(3MGTjI Ydi cJGH aj GdJaSjQs - (3eLghds
(3ChdgG (B:s
(3ChdgG(B: (3bhdg hEfeG bGd HGSe Gddg hde jbd HGddg Edi BNQg, bGd GdfMQjQ GdJaJGRGfj aj TQM JdNjU GdLGeY eG bjd Cf PcQ GdGSe UdI CJj Hg ddJHQc hGdaQb Hjfg hHjf Gdjejf bdjds
(3BNQgG (B:s
(3BNQgG(B: (3bhdg hbjd GdNWGH eY GdCRhGL hdG GJCcjO Gdfaj ceG aj GdhLg GdChd dG ddfgj ceG aj GdhLg GdKGdK(B. (3bhdg(B: (3hGddGJj HUdJgG aj bhdg JYGdi GddGJj ONdJe Hgf bhdg hdGs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs